Nikon D300s for dummies - King, Julie Adair (--For dummies., 2010)
"Your Nikon D300s is known for its awesome performance in low-light conditions, its super-powerful 51-point autofocus system, and the really, really long list of ways you can customize it. This friendly guide is known for making it easy to use every one of these features. Get the scoop here, and you'll start getting excited about what you can create!"--Resource description page.